2021
DOI: 10.1101/2021.03.18.21253902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Smoking and Vaping Among a National Sample of U.S. Adults During the COVID-19 Pandemic

Abstract: IntroductionWith concerns about cigarette smoking being a risk factor for severe disease from COVID-19, understanding nicotine and tobacco use patterns is important for preventive efforts. We aimed to understand changes in product use behaviors among U.S. adult combustible cigarette smokers and electronic cigarette (e-cigarette) users.MethodsIn August 2020, we conducted a cross-sectional survey of a nationally-representative sample of adults age >18 in NORC’s AmeriSpeak Panel who reported past 6-month use o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…A study conducted in Holland found a greater proportion of smokers who reported smoking more compared to those who reported smoking less [ 57 ]. Increased smoking was also observed in China [ 58 ], Australia [ 59 ] and United States [ 60 ]. The increase in smoking behavior during the pandemic can be attributed to increased stress [ 60 ] and physical inactivity [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Holland found a greater proportion of smokers who reported smoking more compared to those who reported smoking less [ 57 ]. Increased smoking was also observed in China [ 58 ], Australia [ 59 ] and United States [ 60 ]. The increase in smoking behavior during the pandemic can be attributed to increased stress [ 60 ] and physical inactivity [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have also reported that a similar proportion of smokers either increased or decreased smoking [ 27 , 31 , 32 , 35 ], while others have found that there was a higher proportion of smokers who increased smoking than reduced smoking [ 13 , 28 , 29 , 37 ]. Some studies only reported on either increasing [ 34 , 38 , 39 ] or decreasing [ 40 , 41 , 42 ] smoking, and these studies have shown highly varied estimates of either behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have examined if smokers tried to quit and/or successfully quit, either during, or because of, COVID-19 [ 30 , 34 , 40 , 43 45 ]. These studies have however reported highly variable estimates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations